ANALISIS MASA TUNGGU MAHASISWA FRESH GRADUATE UNTUK MENCAPAI DREAM JOB - Iqbal, Mohammad Iqbal Fikri Arinda Pradhana; Wildana, Dandy Alif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
At the forefront of change in this very dynamic environment, students are also at the same time as customers in a tertiary institution. In the period of studying there are many things that happen, either caused by internal or external factors of the students themselves. among students in Malang City, especially students of the Faculty of Economics and Business, the dynamics approach in this study is work life balance (WLB). Work life balance (WLB) is not only for students who are already working but who are not yet, because Work life balance (WLB) emphasizes the quality of life for students who have not worked or who will work. This study uses the path analysis method or path analyst which aims to find out whether the X Y and Z variables are related to each other.